Numerical simulation and damage analysis of RC bridge piers reinforced with varying yield strength steel reinforcement. Issue 130 (March 2020) - Su, Junsheng; Li, Zhongxian; Wang, Junjie; Dhakal, Rajesh Prasad
Abstract: A force-based fiber beam-column element was developed to simulate the seismic performance of reinforced concrete (RC) bridge piers reinforced with high-strength steel bars (HSSB) with/without a distinct yield plateau. The finite element model (FEM) adopted in this paper considers cracking and spalling of cover concrete, buckling and low-cycle fatigue of longitudinal steel bars, as well as bond-slip (strain penetration) between longitudinal bars and concrete. A fiber-based damage model based on material strains of concrete and reinforcing steel was used to predict the evolution and progress of damage in RC bridge piers. Two sets of test data of RC specimens were used to verify the applicability of the FEM and the damage model. A parametric analysis was conducted to derive suitable modeling parameters for reinforcing steel to accurately simulate the mechanical properties of HSSB with/without distinct yield plateau, and the resulting seismic performance of RC piers. The FEM used herein could reflect the effects of buckling and low-cycle fatigue of longitudinal steel bars as well as bond slip (strain penetration) on cyclic response of RC piers. The fiber-based damage model was shown to not only predict the damage development progress in RC piers reinforced with HSSB, but also able to convincingly reveal the causes of damage of RC piers with different axial load ratios. Highlights: Fiber-based FEM of RC bridge piers reinforced with HSSB with/without a distinct yield plateau. Effects of bar buckling, low-cycle fatigue and bond slip on cyclic response of RC piers were studied. The increases in buckling length and yield strength of longitudinal bar will intensify pinching response of RC piers. The increase in buckling length will lead to the reduction of low-cycle fatigue life of reinforcing steel. The fiber-based damage model is applicable to damage evaluation of RC piers reinforced with HSSB.